2008
DOI: 10.1093/gerona/63.8.873
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study of Hemoglobin, Race, and Mortality in Elderly Persons

Abstract: Both anemia by WHO criteria and mild reductions in Hb were related to increased risk of mortality in older blacks and whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 22 publications
3
45
0
2
Order By: Relevance
“…4,9,10 It has been suggested that anemia might be masked in some older adults taking diuretics, which can decrease plasma volume, potentially explaining the low-normal hemoglobin concentration to mortality association.…”
Section: Mortality and Hospitalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9,10 It has been suggested that anemia might be masked in some older adults taking diuretics, which can decrease plasma volume, potentially explaining the low-normal hemoglobin concentration to mortality association.…”
Section: Mortality and Hospitalizationmentioning
confidence: 99%
“…[3][4][5] Low-normal hemoglobin concentrations have also been shown to be associated with increased mortality, [5][6][7][8] although this finding is not consistent across studies and depends on the definition of low-normal and the comparison group as well as race/ethnicity and comorbidity. 4,9,10 It has been suggested that anemia might be masked in some older adults taking diuretics, which can decrease plasma volume, potentially explaining the low-normal hemoglobin concentration to mortality association. 11 Alternatively, it is probable that some older adults with low-normal hemoglobin concentrations are more likely to eventually go on to become anemic, potentially increasing their risk of adverse events.…”
Section: Mortality and Hospitalizationmentioning
confidence: 99%
“…Half of the people admitted from their homes do not return there immediately after discharge [5,6]. Recent studies have suggested that anaemia is associated with worse outcomes in the frail and elderly [7,8]. However, the assessment and definitions of anaemia vary as do the outcomes that are reported [9].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos conduzidos em populações idosas nos Estados Unidos, Canadá e em alguns países europeus evidenciaram maior risco de morte entre aqueles com anemia, independentemente de outros fatores relevantes 5,9,18,19,20,21,22 . Além disso, baixos níveis de Hb, independente do diagnóstico de anemia, também apresentaram associação significativa com mortalidade em algumas populações idosas 18,19,21,23 .…”
Section: Introductionunclassified